Deshielding anions enable solvation chemistry control of LiPF6-based electrolyte toward low-temperature lithium-ion batteries - Yuan, Song (2024)
Severe capacity decay under subzero temperatures remains a significant challenge for lithium-ion batteries (LIBs) due to the sluggish interfacial kinetics. Current efforts to mitigate this deteriorating interfacial behavior rely on high-solubility lithium salts (e.g., Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), Lithium bis(fluorosulfonyl)imide (LiFSI))-based electrolytes to construct anion participated solvation structures. However, such electrolytes bring issues of corrosion on the current collector and increased costs. Herein, the most commonly used Lithium hexafluorophosphate (LiPF6 ) instead, to establish a peculiar solvation structure with a high ratio of ion pairs and aggregates by introducing a deshielding NO3 - additive for low-temperature LIBs is utilized. The deshielding anion significantly reduces the energy barrier for interfacial behavior at low temperatures. Benefiting from this, the graphite (Gr) anode retains a high capacity of ≈72.3% at -20 °C, which is far superior to the 32.3% and 19.4% capacity retention of counterpart electrolytes. Moreover, the LiCoO2 /Gr full cell exhibits a stable cycling performance of 100 cycles at -20 °C due to the inhibited lithium plating. This work heralds a new paradigm in LiPF6 -based electrolyte design for LIBs operating at subzero temperatures.